Keadilan I’tidal dalam Akses Kesehatan: Sinergi Maqashid Syariah dan Standar AAAQ bagi Perlindungan Kelompok Minoritas - Nining Handayani; Faiz Karim Fatkhullah (Journal of Innovative and Creativity, 2026)
Systemic discrimination in healthcare access for minority groups constitutes a violation of human dignity rooted in structural inequalities. This normative legal research analyzes the role of the I’tidal principle (equitable justice) within Maqashid Syariah (the objectives of Islamic Law) as a theoretical and practical solution to global and national healthcare marginalization. By juxtaposing international health law standards specifically the Availability, Accessibility, Acceptability, and Quality (AAAQ) framework with contemporary Maqashid Syariah theory, this article explores the operationalization of the protection of life (Hifz an-Nafs). Findings reveal that healthcare failures often stem from a lack of cultural and religious "acceptability," such as inadequate accommodations for hijab, halal nutrition, or gender preferences in medical care. The integration of I’tidal offers an affirmative action model and an ethical framework demanding non-discriminatory treatment as a manifestation of divine trust (amanah). The synergy between Sharia norms and international human rights instruments, such as the ICESCR, creates a dual-protection mechanism that enhances public trust and health outcomes for vulnerable populations. Ultimately, policy transformation toward an inclusive, transparent, and trust-based system is essential to achieving substantive health equity for all societal strata.